Exploiting the interaction between Grp94 and aggregated myocilin to treat glaucoma - Stothert, Andrew R. (Hum Mol Genet, 2014)
Gain-of-function mutations in the olfactomedin domain of the MYOC gene facilitate the toxic accumulation of amyloid-containing myocilin aggregates, hastening the onset of the prevalent ocular disorder primary open-angle glaucoma. Aggregation of wild-type myocilin has been reported in other glaucoma subtypes, suggesting broader relevance of misfolded myocilin across the disease spectrum, but the absence of myocilin does not cause disease. Thus, strategies aimed at eliminating myocilin could be therapeutically relevant for glaucoma. Here, a novel and selective Grp94 inhibitor reduced the levels of several mutant myocilin proteins as well as wild-type myocilin when forced to misfold in cells. This inhibitor rescued mutant myocilin toxicity in primary human trabecular meshwork cells. Mechanistically, in vitro kinetics studies demonstrate that Grp94 recognizes on-pathway aggregates of the myocilin olfactomedin domain (myoc-OLF), accelerates rates of aggregation and co-precipitates with myoc-OLF. These results indicate that aberrant myocilin quaternary structure drives Grp94 recognition, rather than peptide motifs exposed by unfolded protein. Inhibition of Grp94 ameliorates the effects of Grp94-accelerated myoc-OLF aggregation, and Grp94 remains in solution. In cells, when wild-type myocilin is driven to misfold and aggregate, it becomes a client of Grp94 and sensitive to Grp94 inhibition. Taken together, the interaction of Grp94 with myocilin aggregates can be manipulated by cellular environment and genetics; this process can be exploited with Grp94 inhibitors to promote the clearance of toxic forms of myocilin.